Consumer’s Motivation to Purchase Frozen Food in Kathmandu - Dabadi, Sunita; Gurung, Binit (Management Dynamics, 2020)
The purpose of the current study is to identify the motivating factors in purchasing frozen food in Kathmandu. Frozen food is considered one of the growing food industry, and bears the ability to sustain itself in today’s market. The research used casual-comparative and descriptive research design with a quantitative and qualitative approach to get an in-depth understanding of the subject matter. The convenience sampling technique was to collect the data where 156 samples were collected using a survey questionnaire from the consumer who bought frozen food from the department store in the Balaju area of Kathmandu. Along with this in-depth interview was taken with the store representative to find out the highly preferable frozen food. A test of ANOVA was run to understand the relationship between demographic variables and motivation factors and purchase intention. The correlation coefficient was used to test the relationship between dependent and independent variables. Research findings reveal that there is no significant relationship between age, gender, and employment status on motivation factor and purchase intention, however, the finding revealed that there is a significant relationship between education and purchase intention. Similarly, the research uncovered that the consumer’s motivation in regards to purchasing frozen food is highly dependent on intrinsic factors (taste, ingredients, nutritional value, value for money), and extrinsic factors (brand, advertisement, convenience, education). Along with this study also revealed on a household, the most purchase frozen food product is frozen MO: MO and on industrial related with the restaurant and hotels, the most purchased frozen food product is the frozen green peas, French fries, and sweet corn.